2005
DOI: 10.1111/j.1445-5994.2004.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective audit of short‐term concurrent ketamine, opioid and anti‐inflammatory (‘triple‐agent’) therapy for episodes of acute on chronic pain

Abstract: The results suggest that this 'burst' triple-agent approach is safe and effective in an inpatient palliative care population during episodes of poorly controlled acute on chronic pain, and warrants further investigation to ascertain whether it gives superior results compared to the 'gold-standard' WHO ladder approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
1
14
0
2
Order By: Relevance
“…If pain is not treated at the appropriate times, injury to nociceptive nerves and central sensitization may be induced, leading to allodynia and hyperpathia. Hence, Good et al [27] suggested triple-agent therapy involving the co-injection of opioid analgesics, NSAIDs, and ketamine in the early period. This is similar to our method for patients undergoing Nuss surgery, a procedure which induces severe post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
“…If pain is not treated at the appropriate times, injury to nociceptive nerves and central sensitization may be induced, leading to allodynia and hyperpathia. Hence, Good et al [27] suggested triple-agent therapy involving the co-injection of opioid analgesics, NSAIDs, and ketamine in the early period. This is similar to our method for patients undergoing Nuss surgery, a procedure which induces severe post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic management of cancer pain is a sequence of increasing steps for control (Good et al, 2005). In two case studies of patients with escalating and excruciating pain, low-dose ketamine provided analgesia that increasing doses of morphine and hydromorphone failed to achieve (Fine, 1999).…”
Section: Drug Descriptionmentioning
confidence: 98%
“…Severe cancer pain is persistent and interferes with activities of daily living (e.g., eating, sleeping), leading to depression and fatigue (Otto, 2001). According to Good, Tullio, Jackson, Goodchild, and Ashby (2005), the longer cancer pain is not controlled adequately, the more difficult controlling it becomes, as refractory pain later develops.…”
Section: Severe Cancer Painmentioning
confidence: 98%
See 1 more Smart Citation
“…Management involves treating the underlying medical condition as well as the skin and using multiple analgesics to control severe ischaemic pain. 6 Dermatomyositis and malignant melanoma: a rare association that worsens prognosis?…”
Section: Calciphylaxis: Fatal Arteriosclerosis Of Uncertain Mechanismmentioning
confidence: 99%